Penerapan Metode Hafalan Dan Qiro’ah Pada Pelajaran Bahasa Arab Di MAS Hidayah Bandar Khalifah - Syahputri, Diana (EL-EMIR Institute, 2025)
Learning Arabic plays an important role in a Madrasah because it greatly facilitates the understanding of Islamic sources. However, in reality, many students still face difficulties in mastering vocabulary, comprehending texts, and developing reading skills. This study aims to examine the effectiveness of the memorization method (tahfīẓ) and qirā’ah in improving the Arabic language proficiency of grade XI students at MAS Hidayah Bandar Khalifah. The research method used is descriptive qualitative through semi-structured online interviews and literature review. The results of the study show that the main obstacles faced by students include the absence of textbooks, limited mastery of nahwu and shorof rules, low retention of vocabulary, and the monotony of the lecture method applied by teachers. The implementation of the memorization method proved to help students recall vocabulary and strengthen memory, while the qirā’ah method enhanced reading skills and comprehension of Arabic texts. Furthermore, students’ responses to both methods were generally positive, as they were considered more engaging and enjoyable compared to previous methods. Thus, the combination of memorization and qirā’ah methods is effective in improving students’ Arabic proficiency and can serve as an alternative teaching strategy in Madrasah Aliyah.